2006
DOI: 10.1118/1.2349692
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional cone‐beam computed tomography using an on‐board imager

Abstract: On-board cone-beam computed tomography (CBCT) has recently become available to provide volumetric information of a patient in the treatment position, and holds promises for improved target localization and irradiation dose verification. The design of currently available on-board CBCT, however, is far from optimal. Its quality is adversely influenced by many factors, such as scatter, beam hardening, and intra-scanning organ motion. In this work we quantitatively study the influence of organ motion on CBCT imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
152
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 30 publications
(32 reference statements)
0
152
0
Order By: Relevance
“…Within this context, the common metric of contrast‐to‐noise ratio (CNR) may not be suitable, in the sense that a high CNR output may not indicate a better image quality (19) . To quantitatively assess the loss of image quality due to motion for the two imaging protocols, we chose to use CTF and NEQ metrics, eliminating any dependency of contrast measurement on the sample size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the common metric of contrast‐to‐noise ratio (CNR) may not be suitable, in the sense that a high CNR output may not indicate a better image quality (19) . To quantitatively assess the loss of image quality due to motion for the two imaging protocols, we chose to use CTF and NEQ metrics, eliminating any dependency of contrast measurement on the sample size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] There are two methods discussed for reducing the angular spacing in 4DCBCT; one uses multiple rotations around the patient with normal gantry speed, 22,23 and the other uses reduced gantry speed (slow rotation). [23][24][25] It has been concluded that the slower gantry rotation produces superior 4DCBCT images compared with multiple gantry rotation since the multiple gantry rotation method may miss or duplicate projections.…”
mentioning
confidence: 99%
“…Recently, the time synchronized CBCT (4DCBCT) method has been introduced to manage respiration-induced target motion during treatment verification imaging. [22][23][24][25][26][27][28][29][30] In 4DCBCT imaging, two-dimensional (2D) projections acquired at different times and positions are sorted into several groups, according to their respiratory phases, and each phase group is then reconstructed independently to obtain a volumetric image corresponding to that specific phase. The respiratory wave required for retrospective 4DCBCT reconstructions is derived using either 2D projections of CBCT itself or an external surrogate system.…”
mentioning
confidence: 99%
“…), in most cases for a pre-treatment set-up. [14][15][16][17][18] But those approaches have some inconvenient, leading to possible target miss. First, due to the fact that they are associated with external information not directly correlated to the tumor motion; and second, because of the impossibility to asses changes in the amplitude of breathing motion that may occur during some fractions, using only pretreatment imaging verification.…”
Section: Introductionmentioning
confidence: 99%